(untitled) (International journal of medical sciences, 2026)
The modernization of pharmaceutical education requires the integration of innovative pedagogical technologies to enhance professional competencies, clinical reasoning, and digital literacy among students. This study analyzes the effectiveness of modern teaching approaches such as problem-based learning (PBL), case-based learning (CBL), simulation technologies, digital platforms, blended learning, and competency-based education in pharmaceutical training. The research evaluates their impact on students’ academic performance, practical skills, and critical thinking abilities. The findings demonstrate that the integration of innovative pedagogical methods significantly improves learning outcomes and professional readiness in pharmaceutical education.